366 моделей оригами - Сержантова Татьяна Борисовна (Внимание: дети!, 2004)
Экземпляры: ф.11 (2004) / Инвентарный номер: 48393 / Цена: / Сис.шифр: 85.12 / Авт.знак: С 32 / ГРНТИ: 18.31.51 / ББК: 37.248